Efektifitas Metode Amalgamasi dan Metode Flotasi pada Proses Pengolahan Emas di Wilayah Pertambangan Rakyat (WPR) - Yossa Hutajulu; Lisa Virgiyanti; Wisnu Rijati; Fahrul Indrajaya; Yustinus Hendra Wiryanto (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The amalgamation and flotation methods are widely used by miners because the methods are simple, fast and easy. The purpose of this study was aims to test the effectiveness of gold recovery using the amalgamation and flotation methods in conventional gold processing. The research methods used were observation and testing using the amalgamation and flotation methods in conventional gold processing. The effectiveness analysis was carried out by calculating the percentage of gold produced in the amalgamation and flotation processing methods. The test was carried out on 10 samples, each weighing 10 kg. The amalgamation process used a Hg solution, while flotation used a detergent reagent. The total primary gold processing using the amalgamation method was 11.46 grams, while the total primary gold recovery using the flotation method was 12.15 grams. The results of gold processing using the flotation method were higher than those using amalgamation because flotation can separate gold more efficiently from ore containing various impurity minerals. Meanwhile, the amalgamation method, which uses mercury, tends to be less effective and loses some of the gold because it only binds very fine and dispersed gold particles, while flotation can handle ore with lower gold content and larger gold particles.